Improving Employee Well-Being by Means of Virtual Reality – REALEX: An Empirical Case Study - J., Pretsch; E., Pretsch; J., Saretzki; H., Kraus; G. , Grossmann (European Journal of Economics and Business Studies, 2020)
The present paper seeks to analyse how a virtual reality system can foster employee well-being at the workplace. In order to answer the research problem, whether such a system can benefit employees in regards to their well-being, stress perception and relaxation, an empirical case study was conducted. Relevant literature both on the advantages of virtual reality systems in general and on different approaches to fostering employee well-being are displayed and discussed within the paper, leading up to a description of the methodology. Based on a sample of 52 participants from Germany, Austria and Croatia an empirical study with a quantitative, pre- and post-study approach was conducted. Participants were assessed in regards to their initial stress perception, before they used either the REALEX system (a VR based relaxation tool displaying natural landscapes in a virtual reality setting) or a video streaming service on a classical display. The statistical analyses revealed that the usage of the REALEX system was able to significantly improve participants’ stress perception and well-being. In doing so it – also significantly – exceeded the positive effect that the control setting (video streaming) had in these regards. Potential limitations of the study are presented and recommendations both for practical work in the field of human resource management and for scientific research are deducted.